Athlete responses to using a real time optical navigation feedback system during ski training - Kirby, R. (Science and Skiing IV, 2009)
INTRODUCTION: Feedback has been shown to be important for all aspects of motor behavior (Shea et al., 1993) and is our brain's link to the body and to the environment. To date, sport scientists have used video analysis of alpine ski racers as the primary tool for providing athletes with feedback related to technique and tactics. However, many racers and coaches perceive the delay between performance and video feedback (often many hours) as detrimental to the effectiveness of video as a feedback tool. This project investigated the athlete responses to using a real time audible feedback System during training.